EFEKTIVITAS EKSPERIMEN PADA PEGAS MENGGUNAKAN APLIKASI PHYPHOX SEBAGAI MEDIA PEMBELAJARAN - Swita Langi; Djeli Alvi Tulandi; Sixtus Iwan Umbo (Charm Sains: Jurnal Pendidikan Fisika, 2022)
E-practicum is a solution for schools as well as in basic practicums in anticipating learning from home due to the impact of the Covid-19 pandemic. One good application to use is the use of the Phyphox application as a learning medium. This study aims to determine the effectiveness of the Phyphox application in the spring experiment as a learning medium. This research is pre-experimental research with one group pretest-posttest research design. The research subjects are students of the seventh semester of the Physics Department, Manado State University 2020/2021. Collecting data using tests with test instruments in the form of essays and science process skills using rubrics. The average pretest result was 29.50 which increased to an average posttest result of 93.26. The average results of the process skills assessment and affective assessment are in good criteria (66-79%) and very good criteria (80-100%). Obtaining N-Gain scores from each student, there were 19 students in the high N-Gain category with a percentage of 95% and 1 student in the medium N-Gain category with a percentage of 5%. The result of the average N-Gain percentage of 20 students is 89.9%. The results of this study indicate that the use of the Phyphox Application in the spring experiment is effective as a learning medium